Model Skala Prioritas Pembangunan Kota Bandung Berbasis Good Governance - Kurniasih, Dewi (UI Scholars Hub, 2005)
Discussing about the local authonomy, certainly cannot be separated from the financial capacity issue from each local government. This is due to the fact that the authonomy and decentralization are always directly connected with the total of the budget obtained by the local government. Therefore, this matter certainly will be related to the total of the Pendapatan AsliDaerah (PAD) and the percentage towards the APBD. From the description above, the priority scale of the activity is necessary to be arranged. The purposes of the activity are: (1) providing a basic programme of development planning entirely in the local authonomy framework based on the regulation (Undang-Undang) No. 32 Tahun 2004 concerning The Local Gevernment. (2) optimizing the development planning in Bandung through selecting the society’s need. (3) arranging the priority scale of the development activity in Bandung in 2006. The research method used in this paper is explorative descriptive with the quantitative technique by the software usage as one of egovernment applications. The result of the data analysis shows rank of each development activity which will be performed based on the determined criteria as the development priority in Bandung.